Efeito do fluxo salivar na rugosidade e conteúdo mineral do esmalte clareado: estudo in situ e in vitro - Debora Drummond Hauss Monteiro (2020)
This study evaluated the effect of saliva in vitro and regular or low salivary flow in situ on roughness, calcium/phosphorus ratio and calcium and phosphorus percentages of the enamel bleached with 35% hydrogen peroxide. Seventy-five specimens of third molars were divided in 5 groups, G1: Not bleached and not exposed to saliva; G2: Bleached and not exposed to saliva; G3: Bleached and stored in natural saliva in vitro, G4: Bleached and exposed to human saliva in situ in normal salivary flow participants, G5: Bleached and exposed to human saliva in situ in low salivary flow participants. Roughness (Ra, Rz) was evaluated with a 3D laser non-contact profilometer. Calcium/phosphorus ratio and calcium and phosphorus percentages were determined with energy- dispersive X-Ray spectrophotometry. These evaluations were performed before bleaching (T1), after bleaching (T2) and after the contact with saliva (T3). Participants saliva was collected and salivary flow was measured for their allocation in groups 4 and 5. Salivary pH and buffering capacity were evaluated with measuring tapes. Salivary calcium and phosphorus concentrations were determined by absorbance spectrophotometry. Data were analyzed by non parametric tests for the analysis between groups and times. A model of linear regression was adjusted for the dependent variable enamel roughness of groups 4 and 5 in T3, considering the covariables salivary flow, pH, buffering capacity and salivary calcium and phosphorus concentration (p<0.05). Roughness was similar among groups in T1. In T2, G1 differed from all groups. In T3, G5=G2>G3=G4=G1. For G1, roughness of T1=T2=T3. For G2 and G5 T1<T2=T3. For G3, T1<T3<T2; for G4, T1=T3<T2. Considering the calcium/phosphorus ratio and percentages of calcium and phosphorus in enamel, there was not a statistically significant difference between groups (p>0.05), nor between the moments of evaluation T1, T2 and T3 (p>0.05). Ra and Rz were, respectively, 0.14 and 1.95 lower with normal salivary flow than reduced salivary flow. It was concluded that the contact with the human saliva in vitro and normal salivary flow in situ reestablished the enamel roughness to the original values, but the low salivary flow did not. Dental bleaching and the contact with human saliva cannot modify calcium/phosphorus ratio nor their isolated percentages. Recovery of bleached enamel roughness was higher in normal salivary flow than low salivary flow, regardless of saliva pH and buffering capacity.